THE EFFECT OF USING PAIR TAPING TECHNIQUE TOWARD SPEAKING ABILITY IN DESCRIPTIVE TEXT OF THE SECOND YEAR STUDENTS AT A PRIVATE SECONDARY SCHOOL IN PEKANBARU - Intan Septia Latifa (Bandar Lampung University (UBL), 2016)
Learning how to speak English fluently and accurate is always a difficult task for students who learn English as a foreign language. Consequently, it is common to find students who are not used to express opinions in class, some appear conservative and uncomfortable, and rarely ask questions even though they do not understand the content being studied. These problems have also been faced by the students of a private secondary school in Pekanbaru. In this case, implementing a language learning technique called Pair Taping technique is proposed in order to assist learners to cope with those problems. According to the statement above, this study was objected to find the effect of using Pair Taping technique toward speaking ability in the descriptive text. It employed a quantitative method which involving 48 second grade students separated into experimental class and control class. Both classes were given a pre-test and a post-test, which only the experimental class received the treatment by using Pair Taping technique, while control class used the non Pair Taping Technique. The findings affirmed the rejection of the null hypothesis, thus including that Pair Taping technique had a significant effect on students’ speaking ability in descriptive text of the second grade students. This study is essential because it offers implication on teaching and learning process because applying Pair Taping technique provides a challenge for students to be more active and confident in speaking activities. Moreover, it also assists both teachers and students doing a direct evaluation of the speaking task through the recorded audio from taping activities.